2019
DOI: 10.1109/lgrs.2019.2903194
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Vegetation Pixel Classification by Using Convolutional Networks

Abstract: Plant phenology studies rely on long-term monitoring of life cycles of plants. High-resolution unmanned aerial vehicles (UAVs) and near-surface technologies have been used for plant monitoring, demanding the creation of methods capable of locating and identifying plant species through time and space. However, this is a challenging task given the high volume of data, the constant data missing from temporal dataset, the heterogeneity of temporal profiles, the variety of plant visual patterns, and the unclear def… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In this PhD thesis, we proposed solutions that address important challenges related to the exploitation of deep learning into the remote sensing domain, including data availability, context exploitation, and so on. It was completed in approximately four years (from March 2015 to May 2019) and has resulted in four international journal papers [5], [8], [23], [25], and eleven international conference papers [3], [6], [7], [22], [24], [27]- [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this PhD thesis, we proposed solutions that address important challenges related to the exploitation of deep learning into the remote sensing domain, including data availability, context exploitation, and so on. It was completed in approximately four years (from March 2015 to May 2019) and has resulted in four international journal papers [5], [8], [23], [25], and eleven international conference papers [3], [6], [7], [22], [24], [27]- [32].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this argument, new technologies have been proposed toward acquiring aerial images with improved quality, resulting in more advanced satellites launched to observe the Earth, as well as, more recently, in drones and unmanned aerial vehicles. These top-notch Remote Sensing Images (RSIs) may provide useful information that could be employed in several Earth Observation applications, including urban planning [1], crop and forest management [2], [3], disaster relief [4], [5], phenological studies [6]- [8], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mauro et al [30] used a multi-layer perceptron (MLP) and a CNN to classify land cover from multi-temporal Landsat images. Nogueira et al [31] implemented a multi-branch CNN for vegetation mapping and confirmed its superiority to a traditional CNN operating on a temporal stack of images. Pelletier et al [28] proposed a temporal CNN for crop classification where convolutions are applied in the temporal domain.…”
Section: Introductionmentioning
confidence: 92%
“…This section aims to explain all deep learning methods that were evaluated in this work for erosion identification. Such semantic segmentation approaches were selected based on their popularity and performance for different applications and images, including computer vision [8][9][10][11][12][13], remote sensing [5,7,[26][27][28][29][30], medical [31][32][33][34][35], and so on. However, although their success in different domains, as aforementioned, those methods were never evaluated in the erosion identification task.…”
Section: Introductionmentioning
confidence: 99%